Empreendedorismo e crescimento econômico: uma avaliação da performance econômica dos países participantes do Global Entrepreneurship Monitor (GEM) - Barcelos, Bartholomeo Oliveira (2013)
This study aims to analyze the performance of entrepreneurial activity in countries participating in the Global Entrepreneurship Monitor (GEM), by the use of multivariate quantitative methods, in order to generate new thinking about the role of entrepreneurship in the economic growth and development of countries. Therefore, the research is divided into two papers whose approaches are exploratory, due to the potential of the database for the realization of new research, and the achievement of international comparisons of economies. To achieve this goal, the techniques used were the Principal Component Analysis (PCA) and the Cluster Analysis (CA) to study the relationship between the variables and the countries of the data set, thus obtaining an overview of the studied phenomenon. In the study of the variables, eight have been identified as the most representative of GEM s database, making the study of the entrepreneur process more effective. Among the most representative variables, the strong influence of the entrepreneurs´ attitude about the opening rates of new enterprises can be identified. To analyze the countries included in this study a classification of the economic performance of these nations was proposed, by creating a ranking of Entrepreneurial Activity Performance (EAP). The order of the countries was aligned to the methodologies used by both the World Economic Forum (WEF) and the World Bank, for the ranking of economic performance and economic development. Therefore, the study explored the main points of the GEM database, variables and countries, making use of multivariate techniques that provided information for the analysis of global entrepreneurship from a different perspective